Quality of Service from a Network when Using Youtube Application - Marpaung, Noveri Lysbetti; Saputri, Rizka Dwi; Amri, Rahyul (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2022)
Nowadays, utilization of internet services is very important to do all jobs online, especially in pandemic of Corona Virus, whereas all employees from every institution must work from home. Therefore, the number of people using internet services increased dramatically. However, availability of internet network is not enough to complete those tasks. The other mainly important role to arrange all these chores is quality of service of its internet. In addition, other ordinary activity which must be prepared to execute is streaming video about many things. Consequently, all those workers must use YouTube application. Aim of this paper is to determine quality of service in internet network of one private Internet Service Provider company in Pekanbaru, related to real conditions on each of 40 clients, Outputs of this study is qualification of each Throughput, Delay, Packet Loss and QoS Parameters based on TIPHON. Results of the research show that QoS Parameters in this Internet Service Provider are Unsatisfied and tends to be Bad because there are only two users who obtain Satisfied, none of clients procure Very Satisfied, 25 clients experience Bad quality and 13 users face Unsatisfied category when using the internet network.